In vitro Screening of Combined Extracts of Some Medicinal Plants of Indian Origin for Antioxidant and Antibacterial Activity - Ali, Huma; Dixit, Savita (Asian Journal of Chemistry, 2012)
The use of natural products as medicine has been practiced from ancient time in world. With an estimation of WHO that as many as 80 % of world's population rely on herbal traditional medicines as their primary health care. Based on local use of common diseases and ethno-botanical knowledge, an attempt has been made to investigate the antioxidant and antibacterial activity of combined extracts of Aloe barbandesis (leaves), Tinospora cordifolia (stem), Azadirachta indica (leaves) and Ocimum sactum (leaves). In this study the combine extract of selected plant materials, were analyzed for their antioxidant activity by peroxide value method and diphenylpicrylhydrazyl radical scavenging method along with the reference sample ascorbic acid. The extract were further analyzed to determine their total phenolic content by Folin-Ciocalteau method and total flavonoid content by Dowd method along with the reference sample rutin and gallic acid respectively. The extract exhibited significant antioxidant activity, total phenolic and flavonoid content. The combined extract also showed significant antibacterial activity against Escherichia coli, Proteus, Staphylococcus aureus, Staphylococcus cohni, Klebsialla pneumonia. The antibacterial activity was evaluated according to well diffusion method by using gram positive S. aureus, S. cohni and gram negative E. coli, Klebsialla pneumonia, Proteus. The result indicated that the combine extract had maximum antibacterial activity against, Staphylococcus cohni compare to the other microorganism. The extract can be used effectively for medication purposes.